Implementation of the tikrar method in improving the quality of memorization of tahfidz students at ma darul himah kyai abdan magelang - Ahmad Syarif Hidayatullah; Mar’atus Sholikah; Zaenal Abidin; Uswatun Khasanah; Tamrin Subagyo (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to examine the implementation of the tikrar method in improving the quality of Qur’anic memorization among 11th-grade female tahfidz students at MA Darul Himah Kyai Abdan Magelang. The tikrar method emphasizes systematic verse repetition through the stages of nazhar, talaqqi, tikrar, and tasmi’. It has been shown to enhance memory retention, accuracy of recitation, and student confidence. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the success of this method depends largely on student motivation, teacher support, and effective time management. However, obstacles such as boredom, lack of discipline, and academic overload remain challenges. Therefore, adaptive strategies in managing memorization are needed to ensure the sustainability and effectiveness of this method.